Biomechanical effects of joint disc perforation on the temporomandibular joint: a 3D finite element study - Wentong Gao; Jie Lu; Xiang Gao; Jianping Zhou; Hongwei Dai; Min Sun; Jie Xu (BMC, 2023)
Abstract Background Disc perforation (DP) is a severe type of Temporomandibular Disorder (TMD). DP may induce changes in the internal stresses of the temporomandibular joint (TMJ). Herein, this study attempts to investigate the biomechanical effects of different positions and sizes of DP on the TMJ using a biomechanical approach, to explore the mechanical pathogenesis of TMD. Methods Eleven three-dimensional finite element (FE)models of the TMJ were constructed based on CBCT imaging files of a patient with DP on the left side. These models included the disc with anterior displacement and discs with different locations and sizes of perforations on the affected disc. FE methods were conducted on these models. Results Anterior displacement of the disc leads to a significant increase in the maxim von Mises stress (MVMS) in both TMJs, with the affected side exhibiting a more pronounced effect. DP occurring at the posterior band and the junction between the disc and the bilaminar region has a greater impact on the MVMS of both TMJs compared to perforations at other locations. As the size of the perforation increases, both sides of the TMJs exhibit an increase in the magnitude of MVMS. Conclusions Unilateral disc anterior displacement results in an increased stress on both TMJs. Unilateral DP further affects the stress on both sides of the TMJs. TMD is a progressive condition, and timely intervention is necessary in the early stages to prevent the worsening of the condition.